RELIGIOUS LEADERS IN INDONESIA’S DIGITAL PUBLIC SPHERE AND LEGAL RESPONSIBILITY FOR RELIGIOUS EXPRESSION - Clara Ignatia Tobing (Journal of Law and Administrative Science, 2026)
The expansion of digital platforms has transformed religious expression in Indonesia and intensified religion-based identity polarization in the digital public sphere. This study analyzes the legal responsibility of religious leaders who disseminate religious narratives online. Using normative legal research grounded in constitutional law and international human rights law, the study examines Indonesian legal instruments, including the amended Electronic Information and Transactions Law and the new Criminal Code, alongside the International Covenant on Civil and Political Rights. It also considers interfaith digital dialogue practices and selected online sermon examples. The study finds that religious leaders are full legal subjects who bear personal responsibility for the content and foreseeable social impact of their digital religious expression. Religious authority does not exempt them from accountability. The study formulates four parameters for distinguishing protected religious expression from religion-based hate speech: intent, substance, manner and context of dissemination, and potential social impact. These parameters support proportionate enforcement, legal certainty, pluralism, and the prevention of polarization and hate speech in digital environments.